Emotional Spiritual Quotient (ESQ) Model Sebagai Upaya Pencegahan Penyimpangan Perilaku Keagamaan Generasi Muda - Darma, I Wayan Puniya Saktia; Utami, Luh Kadek Dwi; Darmawan, I Wayan Agus; Sugiariani, Ni Made Sri Ratih; Pratiwi, Ari (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
The increasing prevalence of religious behavioral deviations among the younger generation requires an effective preventive method. This study aims to examine the implementation of the habituation method using the ESQ (Emotional Spiritual Quotient) model as a strategy to prevent such deviations. The ESQ model is designed as a tool for mental and spiritual engineering to build strong character and personality. This method is believed to form individuals who are free from the shackles of negative thinking, possess mental resilience in facing problems, and have the personal strength to avoid actions detrimental to themselves and others. Furthermore, this model also aims to build social strength to maintain harmonious relationships with God, other people, and the surrounding environment. These core characteristics developed through the ESQ model are identified as being able to suppress both the internal and external factors that trigger deviant behavior. Therefore, the habituation method based on the ESQ model is proposed as a comprehensive approach to preventing religious behavioral deviations in the younger generation by building an integral foundation of character and spirituality.